I always found derivation to be helpful in remembering. Since this question is tagged as at the middle school level, I assume you've only learned about arithmetic and geometric sequences.
First, remember what these names mean. An arithmetic sequence is a sequence in which consecutive terms are increased by a fixed amount; in other words, it is an additive sequence. If
![a_n](https://tex.z-dn.net/?f=a_n)
is the
![n](https://tex.z-dn.net/?f=n)
th term in the sequence, then the next term
![a_{n+1}](https://tex.z-dn.net/?f=a_%7Bn%2B1%7D)
is a fixed constant (the common difference
![d](https://tex.z-dn.net/?f=d)
) added to the previous term. As a recursive formula, that's
![a_{n+1}=a_n+d](https://tex.z-dn.net/?f=a_%7Bn%2B1%7D%3Da_n%2Bd)
This is the part that's probably easier for you to remember. The explicit formula is easily derived from this definition. Since
![a_{n+1}=a_n+d](https://tex.z-dn.net/?f=a_%7Bn%2B1%7D%3Da_n%2Bd)
, this means that
![a_n=a_{n-1}+d](https://tex.z-dn.net/?f=a_n%3Da_%7Bn-1%7D%2Bd)
, so you plug this into the recursive formula and end up with
![a_{n+1}=(a_{n-1}+d)+d=a_{n-1}+2d](https://tex.z-dn.net/?f=a_%7Bn%2B1%7D%3D%28a_%7Bn-1%7D%2Bd%29%2Bd%3Da_%7Bn-1%7D%2B2d)
You can continue in this pattern, since every term in the sequence follows this rule:
![a_{n+1}=a_{n-1}+2d](https://tex.z-dn.net/?f=a_%7Bn%2B1%7D%3Da_%7Bn-1%7D%2B2d)
![a_{n+1}=(a_{n-2}+d)+2d](https://tex.z-dn.net/?f=a_%7Bn%2B1%7D%3D%28a_%7Bn-2%7D%2Bd%29%2B2d)
![a_{n+1}=a_{n-2}+3d](https://tex.z-dn.net/?f=a_%7Bn%2B1%7D%3Da_%7Bn-2%7D%2B3d)
![a_{n+1}=(a_{n-3}+d)+3d](https://tex.z-dn.net/?f=a_%7Bn%2B1%7D%3D%28a_%7Bn-3%7D%2Bd%29%2B3d)
![a_{n+1}=a_{n-3}+4d](https://tex.z-dn.net/?f=a_%7Bn%2B1%7D%3Da_%7Bn-3%7D%2B4d)
and so on. You start to notice a pattern: the subscript of the earlier term in the sequence (on the right side) and the coefficient of the common difference always add up to
![n+1](https://tex.z-dn.net/?f=n%2B1)
. You have, for example,
![(n-2)+3=n+1](https://tex.z-dn.net/?f=%28n-2%29%2B3%3Dn%2B1)
in the third equation above.
Continuing this pattern, you can write the formula in terms of a known number in the sequence, typically the first one
![a_1](https://tex.z-dn.net/?f=a_1)
. In order for the pattern mentioned above to hold, you would end up with
![a_{n+1}=a_1+nd](https://tex.z-dn.net/?f=a_%7Bn%2B1%7D%3Da_1%2Bnd)
or, shifting the index by one so that the formula gives the
![n](https://tex.z-dn.net/?f=n)
th term explicitly,
![a_n=a_1+(n-1)d](https://tex.z-dn.net/?f=a_n%3Da_1%2B%28n-1%29d)
Now, geometric sequences behave similarly, but instead of changing additively, the terms of the sequence are scaled or changed multiplicatively. In other words, there is some fixed common ratio
![r](https://tex.z-dn.net/?f=r)
between terms that scales the next term in the sequence relative to the previous one. As a recursive formula,
![a_{n+1}=ra_n](https://tex.z-dn.net/?f=a_%7Bn%2B1%7D%3Dra_n)
Well, since
![a_n](https://tex.z-dn.net/?f=a_n)
is just the term after
![a_{n-1}](https://tex.z-dn.net/?f=a_%7Bn-1%7D)
scaled by
![r](https://tex.z-dn.net/?f=r)
, you can write
![a_{n+1}=r(ra_{n-1})=r^2a_{n-1}](https://tex.z-dn.net/?f=a_%7Bn%2B1%7D%3Dr%28ra_%7Bn-1%7D%29%3Dr%5E2a_%7Bn-1%7D)
Doing this again and again, you'll see a similar pattern emerge:
![a_{n+1}=r^2a_{n-1}](https://tex.z-dn.net/?f=a_%7Bn%2B1%7D%3Dr%5E2a_%7Bn-1%7D)
![a_{n+1}=r^2(ra_{n-2})](https://tex.z-dn.net/?f=a_%7Bn%2B1%7D%3Dr%5E2%28ra_%7Bn-2%7D%29)
![a_{n+1}=r^3a_{n-2}](https://tex.z-dn.net/?f=a_%7Bn%2B1%7D%3Dr%5E3a_%7Bn-2%7D)
![a_{n+1}=r^3(ra_{n-3})](https://tex.z-dn.net/?f=a_%7Bn%2B1%7D%3Dr%5E3%28ra_%7Bn-3%7D%29)
![a_{n+1}=r^4a_{n-3}](https://tex.z-dn.net/?f=a_%7Bn%2B1%7D%3Dr%5E4a_%7Bn-3%7D)
and so on. Notice that the subscript and the exponent of the common ratio both add up to
![n+1](https://tex.z-dn.net/?f=n%2B1)
. For instance, in the third equation,
![3+(n-2)=n+1](https://tex.z-dn.net/?f=3%2B%28n-2%29%3Dn%2B1)
. Extrapolating from this, you can write the explicit rule in terms of the first number in the sequence:
![a_{n+1}=r^na_1](https://tex.z-dn.net/?f=a_%7Bn%2B1%7D%3Dr%5Ena_1)
or, to give the formula for
![a_n](https://tex.z-dn.net/?f=a_n)
explicitly,